Synergy of lemon grass and neem leaves as growth promoters on performance, digestibility and carcass yield of broiler finisher (Agriculture, Food, and Natural Resources Journal, 2025)
Herbal plants have been considered as an effective growth promoters feed additive, majorly because of their bioactive compounds. It is on this note that this study was conducted to assess the synergetic effects of lemon grass (LG) and neem leaves (NL) as growth promoter feed additives in broilers' diets. LG and NL were harvested, chopped (2 mm), and air-dried (DM ≥ 75%). The air-dried samples were analyzed for phytochemicals, proximate composition, and selected minerals before being incorporated into the broiler finisher diet at 5% each (T2 and T3) and 2.5% each in the combined treatment (T4). Four diet treatments were formulated to supply an average of 20.73% CP and 3336 kcal/kg ME. Each treatment comprises 3 replicates with 10 birds/replicate. The results show that the plants were rich in flavonoids, phenols, tannins, resins, and terpenoids, while they both had appreciable amounts of sterols and alkaloids. Lemon grass was richer in crude protein, crude fiber, and ash than NL, while the latter was richer in calcium, potassium, and sodium. Inclusion of these plants as feed additives had a significant (P
Keywords: synergetic effects; Lemon grass; neem leaves; broiler chicken; Phytochemicals